China's 40 Years of Fiscal and Tax Reform: A Basic Trajectory. Issue 2 (14th March 2018) - Gao, Peiyong
Abstract: The present paper describes the trajectory of China's fiscal and tax reform in the past 40 years, which can be summarized in five phases. The reform commenced with "decentralizing power and transferring benefits." Then, under great fiscal pressure, institutional reform was instigated, which aimed to establish a new fiscal and tax system. To regulate the government revenue and expenditure beyond the fiscal and tax system, reforms were put in place to build an institutional framework for public finance. As the fiscal and tax reform had gradually entered the more sophisticated phases, China took a series of measures to further improve the public finance system. Since 2012, based on the overall plan of comprehensively deepening reform, China has embarked on establishing a modern public finance system. The present paper characterizes China's fiscal and tax reform as gradually moving toward a system that aligns with the overall reform and complements the goal of marketization and modernization of state governance.